The Impact of Global Interest Rate Policy on Exchange Rate Stability in Developing Countries: A Case Study of Indonesia - Falah, Zidnal; Hardianto, Feri (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
Global interest rate policies, especially those implemented by the Fed and the European Central Bank (ECB), have a significant impact on exchange rate stability in developing countries, including Indonesia. Changes in interest rates in developed countries can trigger capital outflows that weaken the rupiah exchange rate, putting pressure on national economic stability. This study aims to analyze the impact of global interest rate policy on rupiah exchange rate stability in Indonesia and assess the role of domestic monetary policy implemented by Bank Indonesia in maintaining such stability. The method used is multiple linear regression to measure the influence of the Fed, ECB, and BI Rate interest rates on the Rupiah exchange rate, as well as the Granger Causality test to explore the causal relationship between these variables. The results show that the Fed and ECB interest rate hikes each cause significant depreciation of the Rupiah, while the increase in the BI Rate is able to stabilize the exchange rate in the short term. The Granger Causality test also shows a causal relationship between global interest rate hikes and the weakening of the rupiah. This study provides empirical evidence that global interest rate policy affects exchange rate stability in Indonesia, and domestic monetary policy plays an important role in mitigating these external impacts